Renal Fibrosis: SIRT1 Still of Value - Wu, Huailiang; Qiu, Zhen; Wang, Liyan; Li, Wei (Biomedicines, 2024)
Chronic kidney disease (CKD) is a major global health concern. Renal fibrosis, a prevalent outcome regardless of the initial cause, ultimately leads to end-stage renal disease. Glomerulosclerosis and renal interstitial fibrosis are the primary pathological features. Preventing and slowing renal fibrosis are considered effective strategies for delaying CKD progression. However, effective treatments are lacking. Sirtuin 1 (SIRT1), a nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase belonging to class III histone deacetylases, is implicated in the physiological regulation and protection of the kidney and is susceptible to a diverse array of pathological influences, as demonstrated in previous studies. Interestingly, controversial conclusions have emerged as research has progressed. This review provides a comprehensive summary of the current understanding and advancements in the field; specifically, the biological roles and mechanisms of SIRT1 in regulating renal fibrosis progression. These include aspects such as lipid metabolism, epithelial-mesenchymal transition, oxidative stress, aging, inflammation, and autophagy. This manuscript explores the potential of SIRT1 as a therapeutic target for renal fibrosis and offers new perspectives on treatment approaches and prognostic assessments.